Carbon Dioxide (CO2) sequestration by trees and green open space (GOS) at the campus of Pakuan University - Dewi, Indarti Komala; Febriani, Yusi; Wicaksono, Arif (Universitas Pakuan, 2024)
Pakuan University (Unpak) as one of the largest private campuses in Bogor City, is committed to reducing greenhouse gases (GHG) emissions, especially CO2, through green open spaces (GOS) and trees on campus. Currently, the GOS and trees on the Unpak campus have not been arranged by CO2 sequestration as a consideration, even though the source of CO2 on the Unpak campus apart from the number of students which is more than 15,000 people is also filled with motorized vehicles. Therefore, to participate in reducing GHG emissions, especially CO2 in Bogor City, and create a comfortable campus, a campus GOS management strategy is needed which is based on CO2 sequestration. This research aims to analyze the ability of existing trees and GOS to sequester CO2. CO2 sequestration calculations are carried out based on the area of the GOS and the sequestration capacity of the trees in the GOS. The research results show that the 6 zones on Unpak's main campus have different CO2 sequestration capacities depending on the area of space planted with grass and ornamental bushes and the number of trees and shrubs planted. Overall, the CO2 sequestration capacity of trees and GOS on Unpak's main campus is 282,784.89 kg per year. ABSTRAK Universitas Pakuan (Unpak) sebagai salah satu kampus swasta terbesar di Kota Bogor berkomitmen menurunkan emisi gas-gas rumah kaca (GRK), khususnya CO2 melalui ruang terbuka hijau (RTH) dan pepohonan di dalam kampus. Saat ini RTH dan pepohonan di kampus Unpak belum ditata dengan mempertimbangkan sekuestrasi CO2, padahal sumber CO2 di kampus Unpak selain dari jumlah mahasiswa yang lebih dari 15.000 orang juga dipenuhi oleh kendaraan bermotor. Oleh karena itu, untuk ikut serta dalam penurunan emisi GRK khususnya CO2 di Kota Bogor dan mewujudkan kampus yang nyaman diperlukan strategi pengelolaan RTH kampus yang berbasis pada penyerapan CO2. Penelitian ini bertujuan untuk menganalisis kemampuan pepohonan dan RTH yang ada dalam menyerap CO2. Perhitungan sekuestrasi CO2 dilakukan berdasarkan luas RTH dan kapasitas sekuestrasi pohon-pohon yang ada di dalam RTH. Hasil penelitian menunjukkan bahwa 6 zona di kampus induk Unpak mempunyai kapasitas penyerapan CO2 yang berbeda-beda tergantung luas ruang yang ditanami rumput dan semak hias serta jumlah pohon dan perdu yang ditanam. Secara keseluruhan, kapasitas sekuestrasi CO2 pepohonan dan RTH di kampus induk Unpak adalah 282.784,89 kg per tahun.